Mitochondrial division, fusion and degradation. (4th December 2019) - Murata, Daisuke; Arai, Kenta; Iijima, Miho; Sesaki, Hiromi
Abstract: The mitochondrion is an essential organelle for a wide range of cellular processes, including energy production, metabolism, signal transduction and cell death. To execute these functions, mitochondria regulate their size, number, morphology and distribution in cells via mitochondrial division and fusion. In addition, mitochondrial division and fusion control the autophagic degradation of dysfunctional mitochondria to maintain a healthy population. Defects in these dynamic membrane processes are linked to many human diseases that include metabolic syndrome, myopathy and neurodegenerative disorders. In the last several years, our fundamental understanding of mitochondrial fusion, division and degradation has been significantly advanced by high resolution structural analyses, protein-lipid biochemistry, super resolution microscopy and in vivo analyses using animal models. Here, we summarize and discuss this exciting recent progress in the mechanism and function of mitochondrial division and fusion.